2021
DOI: 10.1167/iovs.62.9.29
|View full text |Cite
|
Sign up to set email alerts
|

Activated Blood Coagulation Factor X (FXa) Contributes to the Development of Traumatic PVR Through Promoting RPE Epithelial-Mesenchymal Transition

Abstract: et al. Activated blood coagulation factor X (FXa) contributes to the development of traumatic PVR through promoting RPE epithelial-mesenchymal transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Other growth factors and cytokines such as epidermal growth factor (EGF), TNF-α, interleukin 6 (IL-6), fibroblast growth factor 2 (FGF2), Gremlin or Factor Xa have also been used to induce EMT and study EMT markers, proliferation, migration, and morphology of RPE cells [29,30,37,38]. These models could provide alternatives to the TGF-β-induced EMT model but remain to be more extensively studied.…”
Section: Emt Induction By Growth Factors or Cytokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other growth factors and cytokines such as epidermal growth factor (EGF), TNF-α, interleukin 6 (IL-6), fibroblast growth factor 2 (FGF2), Gremlin or Factor Xa have also been used to induce EMT and study EMT markers, proliferation, migration, and morphology of RPE cells [29,30,37,38]. These models could provide alternatives to the TGF-β-induced EMT model but remain to be more extensively studied.…”
Section: Emt Induction By Growth Factors or Cytokinesmentioning
confidence: 99%
“…Indeed, the proliferative and inflammatory vitreous reaction following the injection of cells, cytokines, growth factors and/or other blood components reproduce different stages of PVR [73,115,116]. In addition, surgical techniques mimicking ocular trauma reproduce the most frequent cause of PVR, disrupting the blood-retinal barrier (BRB), and allowing the subsequent activation and recruitment of macrophages, fibroblasts, and glial cells [37,117]. Interestingly, PVR has also been induced by associating ocular trauma with intravitreal injections or the simultaneous injection of different cell types and/or active compounds [52,70,117,118].…”
Section: Rabbit Pvr Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The early fibrotic appearance of cell is an important part in pathological process of PVR [2] . Some studies have showed that abnormal activation of retinal pigment epithelium (RPE) cells play significant roles in the development of fibrosis during of PVR [3][4][5] . The conversion of RPE cells into fibroblast-like cells accelerates the development of PVR [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, advances in research and data analytics have promoted our understanding and management of ocular trauma. Molecular biology of human tissues and animal models have revealed inflammation with unique molecular pathways in the pathogenesis of various types of ocular trauma ( 2 ). The application of in vivo imaging techniques, such as optical coherence tomography ( 3 ) and adaptive optics laser scanning ophthalmoscopy, has also helped us better understand the mechanism of damage to ocular tissues by external injuries.…”
mentioning
confidence: 99%